(untitled) (Raparin Journal of Humanities (RJH), 2024)
Suspicions regarding the Prophet’s Sunnah and its codification are numerous, including those of the Orientalists. Considering that the Prophet’s Sunnah is the second source of Islamic legislation, it is necessary to respond and eliminate any suspicion raised so as to prevent the realization of those malicious aspirations. From this viewpoint, I provide an overview of Orientalism at the beginning of my paper, delving into the reason for their interest in creating suspicions about the Sunnah and its codification. I have devoted the first chapter to discuss the stages of codifying the Prophet’s Sunnah, by clarifying it in three stage, as the codification of the Prophet’s Sunnah passed through three stages, namely: the stage of codification during the Prophet’s era, then the codification during the era of the Companions, and then the codification during the era of the followers Also known as Al-Tabeen. In the second chapter, I define suspicion and the term Orientalism linguistically and as an idiomatic concept, then I mention a group of suspicions raised by the Orientalists and address them. Finally, the paper concludes, through this modest research, the importance of responding to the suspicions of the Orientalists about the codification of the Prophet’s Sunnah, and that silence and failure to respond to their suspicions increases the gravity of these suspicions, especially in this age, where there is great exposition, many views, and abundant suspicions raised about Islam as a religion, and about the Sunnah and The Prophet as a reliable source in this true religion.